Effect of conduction drying on nutrient and fatty acid profiles: a comparative analysis of hazelnuts and walnuts - Matin, Ana; Brandić, Ivan; Gubor, Mateja; Pezo, Lato; Krička, Tajana; Matin, Božidar; Jurišić, Vanja; Antonović, Alan (Frontiers in Sustainable Food Systems, 2024)
The objective of this study was to investigate the changes in the nutrient and fatty acid profiles of hazelnuts (Corylus avellana) and walnuts (Juglans regia) subjected to continuous drying. Samples from two consecutive years (2020 and 2021) were analyzed for nutritional value both before and after conduction drying. Thermal conduction drying was performed at 60 and 80 °C at intervals of 15, 30, 45, and 60 min. The results showed that hazelnuts had increased ash, protein (from 16.4% to 18.7%), carbohydrate and starch content, while walnuts had a higher pH and fat content (from 60.97% to 71.02%). After drying, increasing temperatures resulted in significant changes in nutrient concentrations for both nuts, including changes in ash, protein, fat (hazelnuts from 58.69% to 71.48% at 60°C for 60 minutes), carbohydrate and starch content, and pH. Monounsaturated and polyunsaturated fatty acid content varied by sample and year, with notable trends such as the increase in oleic acid in walnuts from 82.26% to 83.67%. Longer drying times and higher temperatures correlated with an increase in monounsaturated fatty acids and a decrease in polyunsaturated fatty acids in both nut types. In conclusion, conduction drying, especially at higher temperatures and longer durations, significantly affects the nutrient and fatty acid profiles of hazelnuts and walnuts. The study provides new insights into the effects of drying conditions on the nutrient composition and fatty acid profiles of hazelnuts and walnuts and reveals significant changes that warrant further investigation. It sets the stage for future research to extend these findings to other nut species and alternative drying processes and highlights the importance of optimizing processing parameters for improved health benefits and sustainability.